CALCIUM PHOSPHATE CEMENT-BASED FILLER FOR LACUNAR FISSURE - KOMURA TAKASHI; RAKUKI MASAMI; SOFUE SHIZUO; OOTSUCHI TSUTOMU (1990)
PURPOSE:To obtain the subject filler for lacunar fissures, consisting of tetracalcium phosphate powder, a fluoride, aqueous solution of an organic acid and aqueous solution of an unsaturated carboxylic acid copolymer and capable of protecting molars just after eruption from dental caries and promoting maturation of dentine even after eruption thereof. CONSTITUTION:A calcium phosphate cement-based filler for lacunar fissures consisting of tetracalcium phosphate powder, a fluoride (especially calcium fluoride or strontium fluoride), an aqueous solution of an organic acid (especially preferably malic acid or tricarballylic acid) and an aqueous solution of an unsaturated carboxylic acid copolymer (especially preferably acrylic aciditaconic acid copolymer). The filler for the lacunar fissures can be applied even to teeth just after eruption and cured even under simple moistureproofing conditions and has also promoting action on maturation of dentine after the eruption. Furthermore, the filler has action on recalcification of initial carious lesions and also reinforcement of the dentine.